Screening for antiparasitic activity of crude extracts of Pleurotus highking, a Bangladeshi edible mushroom (Bangladesh Pharmaceutical Journal, 2015)
Compounds obtained from natural sources play significant role to identify various novel drug molecules. This study was designed to investigate parasitic susceptibility of methanolic extract from the Pleurotus highking, an edible mushroom commercially cultivated in Bangladesh against Pheretima posthuma. Extraction was carried out by continuous hot percolation method using methanol as a solvent. Four concentrations (10, 20, 40 and 80 mg/ml) of the extract were used for screening and results were expressed in terms of the time paralysis and death of worms. The extract exhibited promising antiparasitic activity at the concentration of 80 mg/ml. Albendazole and distilled water were used as reference standard and control, respectively. The extract showed its activity in the dose and time dependent manner. This is the first report of the antiparasitic activity of methanolic extract of P. highking.Bangladesh Pharmaceutical Journal 18(1): 38-41, 2015